posted by linds .
express this in sinx
(1/ cscx + cotx )+ (1/cscx- cotx)
i got 2sinx is that right??
express in cosx
problem: is 1 + cotx/cscx - sin^2x
i get to the step of 1 + cos-sin^2x and im stuck..help!
(1/cscx + cotx) + (1/cscx - cotx) =
(sinx + cosx/sinx) + (sinx - cosx/sinx) =
You are correct on that one!
Note: 1 - sin^2x = cos^2x
1 + cotx/cscx - sin^2x =
1 + cosx - sin^2x =
cos^2x + cosx
cosx (cosx + 1)
I hope this helps.
somebody posted the same question before, but they had it as
1/(cscx+cotx) + 1/(cscx - cotx)
this would reduce to 2csc x
which in terms of sinx would be 2/sinx
csc2x + 1 = 0